PENGARUH PEMBERIAN EKSTRAK KAYU SECANG (Caesalpinia sappan L.) SECARA ORAL TERHADAP PROFIL FARMAKOKINETIKA PARASETAMOL PADA TIKUS JANTAN GALUR SPRAGUE-DAWLEY - Annisa Ayu Nur Hakim (2023)
Paracetamol is an over-the-counter drug widely used but often underestimated for its side effects, which contribute to drug poisoning cases worldwide. Sappan heartwood, consumed by Indonesian, contains flavonoids and phenols that may negatively affect the metabolism, efficacy, and toxicity of drugs, including paracetamol. To investigate this, a study examined the pharmacokinetic profile of paracetamol when administered simultaneously with sappan heartwood extract at 294 mg/kg body weight in male Sprague-Dawley rats. The rats were divided into three groups: control, normal, and treatment groups, each with six rats. Blood samples were taken from the rat's lateral tail veins, and spectrophotometric methods were used to determine paracetamol levels. Pharmacokinetic parameters (Ka, Tmax, Cmax, AUC, Vd, Cl, Ke, and T1/2) were calculated based on paracetamol concentration in the blood over time. The results showed that the co-administration of sappan heartwood extract with paracetamol significantly increased the volume of distribution (Vd) by 453.10% (p<0.05). Other parameters also showed an increase, but they were not statistically significant (p>0.05), such as Ka by 43.551%, Cl by 286.743%, Cmax by 214.860%, Tmax by 10.133%, Ke by 28.913%, T1/2 by 935.941%, and AUC by 38.529%.